The fallacy of identification by neutralization in the light of non-cytopathic effect producing enterovirus strains (2017)
We describe the characterization of an enterovirus isolate recovered from untreated raw sewage in Ibadan, southwest Nigeria in 2010. The isolate was neutralized by specific antisera and consequently identified as Echovirus 7 (E7). Subsequent molecular characterization showed the isolate to be a mixture of E7 and Coxsackievirus A24 (CV-A24) thereby suggesting the CV-A24 strain to be non-cytopathic effect producing. It is therefore crucial that identities of enterovirus strains determined by neutralization assay be verified by molecular characterization to ensure they do not have any non-cytopathic effect producing strain(s) lurking unnoticed.